Interferon-Gamma DNA Methylation Is Affected by Mycophenolic Acid but Not by Tacrolimus after T-Cell Activation - Peters, Fleur S.; Peeters, Annemiek M. A.; Hofland, Leo J.; Betjes, Michiel G. H.; Boer, Karin; Baan, Carla C. (Frontiers in Immunology, 2017)
Immunosuppressive drug therapy is required to treat patients with autoimmune disease and patients who have undergone organ transplantation. The main targets of the immunosuppressive drugs tacrolimus and mycophenolic acid (MPA; the active metabolite of mycophenolate mofetil) are T cells. It is currently unknown whether these immunosuppressive drugs have an effect on DNA methylation - an epigenetic regulator of cellular function. Here, we determined the effect of tacrolimus and MPA on DNA methylation of the gene promoter region of interferon gamma (IFNγ), a pro-inflammatory cytokine. Total T cells, naive T cells (CCR7+CD45RO-) and memory T cells (CD45RO+ and CCR7-CD45RO-) were isolated from CMV seropositive healthy controls and stimulated with α-CD3/CD28 in the presence or absence of tacrolimus or MPA. DNA methylation of the IFNγ promoter region was quantified by pyrosequencing at 4 hours, day 1, 3 and 4 after stimulation. In parallel, T-cell differentiation, and IFNγ protein production were analyzed by flow cytometry at day 1 and 3 after stimulation. Our results show that MPA induced changes in IFNγ DNA methylation of naive T cells; MPA counteracted the decrease in methylation after stimulation. Tacrolimus did not affect IFNγ DNA methylation of naive T cells. In the memory T cells, both immunosuppressive drugs did not affect IFNγ DNA methylation. Differentiation of naive T cells into a central-memory-like phenotype (CD45RO+) was inhibited by both immunosuppressive drugs, while differentiation of memory T cells remained unaffected by both MPA and tacrolimus. IFNγ protein production was suppressed by tacrolimus. Our results demonstrate that MPA influenced IFNγ DNA methylation of naive T cells after stimulation of T cells, while tacrolimus had no effect. Both tacrolimus and MPA did not affect IFNγ DNA methylation of memory T cells.